EVALUATION OF ANTIBIOTIC IN ACUTE LYMPHOBLASTIC LEUKEMIA PATIENTS WITH FEBRILE NEUTROPENIA - Ambar Yunita Nugraheni; Safira Salsabilla Rizki Rahardiani (Universitas Muhammadiyah Magelang, 2020)
Patients with hematological malignancy have a high risk of experiencing febrile neutropenia (FN). Acute Lymphoblastic Leukemia (ALL) became one of the most cases as a cause of FN. Chemotherapy can also cause of neutropenia in almost 90% of cases and can increase the risk of developing febrile neutropenia. The administration of irrational antibiotics can cause problems such as increased side effects and resistance. The purpose of this study is to determine the rationality of antibiotics in ALL with FN patients at hospital X Surakarta. This study was an observational study with retrospectively. The research sample was met the inclusion criteria 31 patients with the purposive sampling method. Data were analyzed descriptively. An evaluation antibiotic of 31 patients ALL with FN was obtained the right indication 100% (31 patients), the right patient 100% (31 patients), the right medicine 83,87% (26 patients) and the right dose 51,61% (16 patients). The rationality of antibiotics was 51,61% (16 patients).